Efektivitas Dana Zis Dalam Pemberdayaan Mustahik Melalui Program Master Di Lazismu Kalimantan Barat - Rahmah Yulisa Kalbarini (Jurnal Ilmiah Ekonomi Islam, 2022)
Abstract Abstract.Effectiveness of Zis Fund in Empowering Mustahik through the MASTER’s Program in Lazismu West Kalimantan. This study aims to explain the effectiveness of the utilization of zis fund in empowering the mustahik in Lazismu West Kalimantan in the empowerment program that has been intensified since 2017. The approach that researchers use is a qualitative descriptive approach. The method of data collection was carried out by direct observation to Lazismu West Kalimantan and the location of the mustahik establishment, then conducting interviews directly to Amil in Lazismu, West Kalimantan and mustahik beneficiaries of the Lazismu West Kalimantan program. The results showed that Lazismu West Kalimantan has managed utilize zis funds effectively. It is seen from fulfillment of effectiveness indicators that is program objectives, program accuracy, program socialization and monitoring. The impact of this utilization is mustahik can improve their economy, buy small and big commodities and can save their money fot the future.